Dimensions of a theoretical model of entrepreneurial university (Research, Society and Development, 2023)
In recent years, studies at the Entrepreneurial University (EU) have represented a great research opportunity, seeking its characterization and development. The concepts and elements point to a multilevel phenomenon that involves the participation of a comprehensive set of actors and variables at the systemic, organizational, and individual levels. Given the interrelationship of the elements that make up the EU, the overall objective of this research was to analyze the dimensions that involve the EU as a whole, aiming to provide a holistic view of the phenomenon. With that in mind, a theoretical EU model associated with the indicators of the EU Ranking, organized by the Brazilian Confederation of Junior Enterprises, was applied to analyze the following dimensions: entrepreneurial culture, infrastructure, innovation, extension, internationalization, and financial capital in the context of a ty Brazilian public federal university. The research was qualitative, and exploratory and entailed a single case study. The results showed that the faculty and students are proactive.  However, the university still needs to increase the offer of curricular units and training programs that support and develop its entrepreneurial culture. The need to implement formal environments that specifically support entrepreneurship and consolidate its innovation policy was also identified. These data will enable managers to identify potential areas for the development of academic entrepreneurship, as well as  encourage other universities to likewise engage in data collection.